Acceleration of pCASL-Based Cerebral 4D MR Angiography Using Compressed SENSE: A Comparison With SENSE - Wang, Maoxue; Ma, Yiming; Chen, Fei; Zhou, Fei; Zhang, Jilei; Zhang, Bing (Frontiers in Neurology, 2022)
Objectives: To accelerate noncontrast-enhanced four-dimensional magnetic resonance angiography (4D MRA) based on pseudocontinuous arterial spin labeling combined with the Keyhole and View-sharing (4D-PACK) procedure using Compressed SENSE (C-SENSE) and to improve intracranial vasculopathy evaluations for clinical purposes. Methods: 4D-PACK acquisition with different C-SENSE and SENSE acceleration factors was performed on 29 healthy volunteers and 6 patients by means of a 3.0T MR system. Two radiologists used a 4-grade scale to qualitatively assess vessel visualization of the middle cerebral artery (MCA) and used a 5-grade scale to qualitatively examine the image quality of 4D-PACK axial source images. Interobserver agreement was assessed by determining the weighted kappa statistic. The contrast-to-noise ratio (CNR) and arterial transmit time (ATT) were calculated in four segments of the MCA. Repeated measures one-way ANOVA for CNR and Friedman test for source images and vessel visualization were used to analyse the differences in five sequences. Results: 1) At the M4 segment, C-SENSE5 acquisition (scores, 2.72±0.53) and C-SENSE6.5 (scores, 2.55±0.57) provided similar vessel visualization compared with SENSE4.5 (scores, 2.72±0.46); however, C-SENSE8 (scores, 1.79±0.49) and C-SENSE10 (scores, 1.52±0.51) had lower scores (P<0.050). 2) The source image quality of C-SENSE5 (scores, 4.55±0.51), C-SENSE6.5 (scores, 4.03±0.33) and C-SENSE8 (scores, 3.48±0.51) acquisition was higher than that of SENSE4.5 (scores, 3.07±0.26) (P<0.001). 3) CNRs of different MCA segments for C-SENSE5 and C-SENSE6.5 acquisitions were not significantly different compared with that of SENSE4.5 acquisition. However, the CNRs were significantly lower for C-SENSE8 (M1: 45.85 ± 13.91, M2: 27.08 ± 9.92, M4: 7.93±4.49) and C-SENSE10 (M1: 37.94 ± 9.92, M2: 23.51 ± 9.0, M4: 6.78±4.12) than for SENSE4.5 (M1: 55.49 ± 13.39, M2: 36.94 ± 11.02, M4: 10.18±5.15) in each corresponding segment (P<0.050). ATTs in all MCA segments within different accelerating C-SENSE factors were obviously correlated with SENSE4.5. Conclusions: C-SENSE6.5 acquisition could be used to evaluate both the intracranial macrovascular and distal arteries, which could reduce the acquisition time by 18% (5 min 5 s) compared with SENSE4.5. Moreover, C-SENSE8 acquisition (37% acceleration, 3 min 54 s) could be used for routine screening and clinical diagnosis of intracranial macrovascular disease with balanced image quality.